2021
DOI: 10.1063/5.0054430
|View full text |Cite
|
Sign up to set email alerts
|

Air swirl effect on spray characteristics and droplet dispersion in a twin-jet crossflow airblast injector

Abstract: Spray characterization in a novel twin-jet airblast injector is reported in this paper with the focus on the study of the effect of injector air swirl on droplet characteristics and dispersion behavior. The operational principle of the injector is based on achieving atomization of two liquid jets, injected in a radially opposite direction from a central hub by high-speed annular swirling cross-stream flow of air. Liquid jet atomization within model atomizers and the resulting spray study have not gained much a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…A few researchers (Merkle et al. 2003; Rajamanickam & Basu 2017; Kumar & Sahu 2019; Patil & Sahu 2021; Soni & Kolhe 2021) have examined the characteristics of swirl flow using high-speed imaging and particle image velocimetry (PIV) techniques. The droplet morphology and breakup phenomenon in a swirling airflow is more complex than in a straight airflow without a swirl.…”
Section: Introductionmentioning
confidence: 99%
“…A few researchers (Merkle et al. 2003; Rajamanickam & Basu 2017; Kumar & Sahu 2019; Patil & Sahu 2021; Soni & Kolhe 2021) have examined the characteristics of swirl flow using high-speed imaging and particle image velocimetry (PIV) techniques. The droplet morphology and breakup phenomenon in a swirling airflow is more complex than in a straight airflow without a swirl.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no numerical studies can be found for the nasal spray application that resolves all the complex physics involved in primary atomization. Although, there are studies that have investigated breakup mechanisms from swirl atomizers (Patil and Sahu, 2021;Sahu et al, 2022;Kuo and Trujillo, 2022) and other atomizers such as hollow cones (Di Martino et al, 2022), air-blast (Patil and Sahu, 2021), and coaxial (Kumar and Sahu, 2020;Charalampous et al, 2019). Further computational studies of nasal spray applications can be used to provide a deeper understanding of the primary breakup of the liquid sheet which influences and secondary break-up of a nasal spray and eventually the droplet characteristics.…”
Section: Introductionmentioning
confidence: 99%